(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine the international humanitarian law regulations on child soldiers involved in the armed conflict between the countries of Iraq-Syria and the Islamic State of Iraq and Syria (ISIS) and to determine the legal protection for children as victims of child soldier recruitment from the perspective of International Humanitarian Law. This study uses a normative legal type that is descriptive analysis. This study also uses primary, secondary and tertiary legal materials, where primary legal materials are legally binding materials, secondary materials are additional data from written sources, and finally tertiary legal materials in the form of legal dictionaries, the Great Dictionary of the Indonesian Language, and encyclopedias. The results of this study are that the humanitarian law regulations on child soldiers involved in the armed conflict between the Islamic State of Iraq and Syria and the State of Iraq and Syria clearly violate the provisions of the Optional Protocol to the Convention on the Rights of the Child, the Geneva Conventions, and the Rome Statute of the International Criminal Court, which explicitly prohibit the involvement of children under the age of 15 in armed conflict and categorize it as a war crime. Legal protection for children involved should not be treated as perpetrators of crimes, but should be viewed as victims who have the right to protection, recovery, and social reintegration. This legal protection includes the right to physical and psychological recovery, the right not to be criminalized for actions carried out under duress, and the right to justice that is in the best interests of the child. Input from researchers should be that countries such as Iraq and Syria need to strengthen the implementation of international humanitarian law provisions, especially those related to the protection of children in armed conflict. And also protection of children as victims does not only include prevention, but also rehabilitation and social reintegration. Abstrak penelitian ini bertujuan Untuk mengetahui pengaturan hukum humaniter internasional tentang tentara anak yang terlibat dalam konflik bersenjata antara negara Irak-Suriah dan Islamic State of Iraq and Syria (ISIS) dan Untuk mengetahui perlindungan hukum bagi anak selaku korban perekrutan tentara anak ditinjau Perspektif Hukum Humaniter Internasional. Penelitian kali ini menggunakan tipe yuridis normatif yang bersifat deskriptif analisis. Penelitian ini juga menggunakan bahan hukum primer, sekunder dan tersier, yang dimana bahan hukum primer merupakan bahan yang berkekuatan hukum serta mengikat, bahan sekunder merupakan data tambahan berasal dari sumber tertulis, terakhir bahan hukum tersier berupa kamus hukum, kamus besar Bahasa Indonesia, dan ensiklopedia. Hasil dari penelitian ini yaitu pengaturan hukum humaniter tentang tantara anak yang terlibat dalam konflik bersenjata antara Islamic state of Iraq and suriah dan negara irak suriah secara nyata melanggar ketentuan Protokol Opsional Konvensi Hak Anak, Konvensi Jenewa, serta Statuta Roma Mahkamah Pidana Internasional, yang secara eksplisit melarang keterlibatan anak di bawah usia 15 tahun dalam konflik bersenjata dan mengategorikannya sebagai kejahatan perang. Perlindungan hukum bagi anak yang terlibat tidak boleh diperlakukan sebagai pelaku kejahatan, tetapi harus dipandang sebagai korban yang berhak atas perlindungan, pemulihan, serta reintegrasi sosial. Perlindungan hukum ini mencakup hak atas pemulihan fisik dan psikologis, hak untuk tidak dikriminalisasi atas tindakan yang dilakukan di bawah paksaan, serta hak atas keadilan yang berpihak pada kepentingan terbaik anak Masukan dari peneliti sebaiknya negara seperti irak dan suriah perlu memperkuat implementassi ketentuan hukum humaniter internasional, khususnya yang berkaitan dengan perlindungan anak dalam konflik bersenjata. Dan juga perlindungan terhadap anak-anak sebagai korban tidak hanya mencakup pencegahan, tetapi juga rehabilitasi dan reintegrasi sosial.